Comparison of DTPA and MAG3 renal scintigraphies in terms of differential renal function based on DMSA renal scintigraphy - Demirel, Bedriye Busra; Balci, Tansel Ansal; Tasdemir, Bekir; Koc, Zehra Pinar (Professional Medical Publications, 2012)
Objective: Renal scintigraphy has privileges in imaging methods in terms of providing functional information. Technetium-99m dimercaptosuccinic acid (Tc-99m DMSA) used in imaging of renal parenchyma is the most reliable radiopharmaceutical in the calculation of differential renal function (DRF). In this study, it was aimed to compare the agents of dynamic renal scintigraphy such as Technetium-99m diethylenetriamine pentaacetic acid (Tc-99m DTPA) and Technetium-99m mercaptoacethyltriglycine (Tc-99m MAG3) based on Tc-99m DMSA in terms of DRF. Methodology: Tc-99m DTPA and Tc-99m DMSA scintigraphies were performed in Group A; Tc-99m MAG3 and Tc-99m DMSA scintigraphies were performed in Group B. There were 57 patients [23 F, 34 M; mean age: 18.8 +/- 17.1 years old (range: 3 months-60 years)] in Group A and 30 patients [15 F, 15 M; mean age: 15.7 +/- 14.8 years old (range: 3 months-59 years)] in Group B. The DRF values calculated with Tc-99m DTPA and Tc-99m MAG3 were statistically compared with Tc-99m DMSA. Results: Both Tc-99m DTPA and Tc-99m MAG3 were found quite concordant with Tc-99m DMSA in terms of DRF (p= 0.968, R2= 0.94 and p= 0.989, R2= 0.98, respectively). Conclusions: Despite the fact that DMSA is accepted as the most reliable radiopharmaceutical in the determination of DRF, the reliable results are also obtained in dynamic renal scintigraphy which was carried out with DTPA or MAG3. In addition, the functional status of the kidney could be determined with these techniques. MAG3 scintigraphy may be mainly preferred because of giving better information than DTPA about both the function of the kidneys and the structure of the renal parenchyma.
Keywords: Tc-99m DMSA; Tc-99m DTPA; Tc-99m MAG3